FORMATION OF STUDENT CHARACTER IN LEADERSHIP AND ISLAM AT THE ISLAMIC STUDENT ASSOCIATION OF THE COMMISSARIAT FIS UNIMED HMI DELI SERDANG - Fadli, Muhammad; Maswita (Edelweiss : Journal Of Innovation In Educational Research, 2025)
The Islamic Student Association (HMI), established on February 5, 1947, plays an important role in shaping character, instilling Islamic values, and building the spirit of student leadership. Through structured cadres such as Cadre Training I, II, and III, HMI aims to produce academic personnel based on Islam. This study examines the formation of character and cadre strategies in HMI Commissariat FIS UNIMED, especially in facing the challenges of low student interest, organizational stigma, and time management. The research uses a qualitative approach to Spradley's ethnography, involving observation and interviews. HMI's recruitment strategy includes the use of social media, regular discussions, social activities, and a personal approach. The week-long Cadre I training is a hallmark of HMI Deli Serdang Branch to instill organizational values in depth. Follow-up was carried out to strengthen the understanding of cadres. In conclusion, HMI Commissariat FIS UNIMED remains relevant as an organization for the development of Islamic students through structured cadres and innovative recruitment strategies that produce qualified cadres with a leadership spirit.